Cryo-braking using penetrators for enhanced capabilities for the potential landing of payloads on icy solar system objects. (March 2018) - Winglee, R.M.; Robinson, T.; Danner, M.; Koch, J.
Abstract: The icy moons of Jupiter and Saturn are important astrobiology targets. Access to the surface of these worlds is made difficult by the high ΔV requirements which is typically in the hypervelocity range. Passive braking systems cannot be used due to the lack of an atmosphere, and active braking by rockets significantly adds to the missions costs. This paper demonstrates that a two-stage landing system can overcome these problems and provide significant improvements in the payload fraction that can be landed The first stage involves a hypervelocity impactor which is designed to penetrate to a depth of a few tens of meters. This interaction is the cryo-breaking component and is examined through laboratory experiments, empirical relations and modeling. The resultant ice-particle cloud creates a transient artificial atmosphere that can be used to enable passive braking of the second stage payload dd, with a substantially higher mass payload fraction than possible with a rocket landing system. It is shown that a hollow cylinder design for the impactor can more efficiently eject the material upwards in a solid cone of ice particles relative to solid impactors such as spheres or spikes. The ejected mass is shown to be of the order of 10 3 to 10 4 times the mass of the impactor. The modeling indicates that a 10 kg payload with a braking system of 3 m 2 (i.e. an areal density of 0.3 kg/m 2 ) is sufficient to allow the landing of the payload with the deceleration limited to less than 2000 g 's. Modern electronics can withstand this deceleration and as such the system provides an important alternative to landing payloads on icy solar system objects. Highlights: Soft payload development for icy solar systems objects. No active landing requires are needed for even hypervelocity entry conditions. Payload fraction can be nearly a factor of 5 over active landing systems. Eliminates scorching of the surface while providing exposure of subsurface material.